KORELASI ASPEK PENGETAHUAN DAN SIKAP KELUARGA TERHADAP TINDAKAN PENCEGAHAN DEMAM BERDARAH DENGUE - Nurjanah, Nourma; Inayati, Inna Noor; Salamung, Niswa; Wahyudi, Teguh; Zen, Suharno (Ensiklopedia of Journal, 2024)
Abstract: DHF is a public health problem that tends to be increasingly widespread, in line with the increasing flow of transportation and population density. This disease is found in almost all parts of the world, especially in tropical and subtropical countries both endemically with outbreaks associated with the arrival of the rainy season. The purpose of this study was to determine the Relationship between Family Knowledge and Attitudes towards Preventive Measures for Dengue Hemorrhagic Fever in the Pusako Health Center Working Area. This type of research is quantitative research with research design used cross sectioanal research design with a total sample of 93 people. Data analysis used chi square test analysis. The results showed that there was a significant relationship between knowledge (p value 0.002) and attitudes (p value 0.000) towards dengue disease prevention measures in the Bantan Health Center Working Area in 2022. It is recommended that respondents can expand their knowledge even more about the prevention of dengue disease for future life through guidance by health workers, especially about the prevention of dengue disease.Keywords: DHF, Knowledge, Attitude